NEPAD welcomes launch of the Biosciences eastern and central Africa Hub - International Livestock Research Institute (International Livestock Research Institute, 2010)
Speaking at the launch of the Biosciences eastern and central Africa (BecA) ILRI Hub on 5 November 2010, Aggrey Ambali of the New Partnership for Africa’s Development (NEPAD) refects on the importance of research to address problems of hunger, low agricultural productivity, rapid population growth and natural and human made disasters.